Rudiments of axiology for sustainable tourism - Klimska, Agnieszka; Klimková, Andrea; Leźnicki, Marcin (Studia Ecologiae et Bioethicae, 2018)
The present article raises the question of sustainable tourism in Poland and Slovakia, highlighting its significance, as well as its objectives and tasks. The situation of tourism in Poland is presented in relation to the issues of spatial economy, whereas Slovak example concentrates mainly on the importance of cultural heritage. Both interrelated aspects were considered crucial for the development of sustainable tourism. Pointing to the noticeably unsustainable character of modern tourism, the authors emphasized the urgent need to refer to ethical and axiological arguments in the process of implementing the principles of sustainable development and spatial order to tourism.